The functional state of the rowing kayaks (boys) athletes in the simulation of training activities - Богуш, Владимир; Гетманцев, Сергей; Кувалдина, Ольга; Косенчук, Александр; Яцунский, Евгений (Slobozhanskyi Herald of Science and Sport, 2018)
Volodymyr Bogush, Sergiy Getmantsev, Olga Kuvaldina, Oleksandr Kosenchuk & Yevgen Yatsunskiy Purpose: to conduct a comprehensive study of the functional status of athletes (boys) of various age groups specializing in rowing, for the possible subsequent determination of prospects in this sport. Material & Methods: athletes of various age groups (11–12 years old, 13–14 years old, 15–16 years old, 17–18 years old) and sports qualifications were surveyed, in total 95 people, according to our method of measuring the effect of a training action, and also visual-motor hearing and motor reactions, the level of musculo-articular sensitivity and coordination of movements, the power of forced inhalation and exhalation. Results: studies have allowed us to study the functional state of athletes. The optimal structure of sports activities contributes to the improvement of all its components, which in the early stages and due to the age characteristics of athletes, as well as the patterns of development of motor skills do not significantly affect the level of results, but have a great impact on the appearance of the corresponding functional basis, especially in the early age periods realization of individual capabilities. Features of the reaction of the body of athletes are a manifestation of effective individual adaptation to intense and complex stimuli of training and competitive activity. The functional state of athletes is determined by the level of development of various physical qualities, coordination abilities, properties of the nervous system, the optimal combination of which is characteristic of each particular sport and allows you to specifically choose sports specialization. Conclusion: the proposed tests for measuring the effect of the training action, electromyoreflexometry, pneumotachometry and reverse dynamometry are sufficiently informative in sports practice and allow us to determine and evaluate the individual prerequisites for sporting achievements. The obtained parameters of the functional state allow you to identify the individual characteristics of the athlete’s body, the possibility of their correction and management of the training process. Conducted comprehensive examinations of the psycho-physiological and functional characteristics of the body of athletes rowers allow you to create methods for assessing the prospects of athletes in their chosen sport.